Analisis Perbandingan Metode Local Search dan Population Based Dalam Algoritma Berevolusi untuk Penyelesaian Travelling Salesman Problem (TSP) - Erdiwansyah Erdiwansyah (Fakultas Teknik, 2016)
Traveling Salesman Problem (TSP) is an optimization problems that can be applied to a variety of activities such as distribution of goods, making burning electricity bills and scheduling. TSP optimization problem in a very famous and has become the standard to try algorithm komputational. Local search algorithm is a method of finding a solution based on the neighborhood of the initial solution. This method is known as iterative improvement. While a search algorithm Based Population global with out considering the surrounding solution. Results showed local search algorithm is better than algorithm-based population in the search for optimal value. However, population-based superior in diversity.